2015
DOI: 10.1177/0300060515583078
|View full text |Cite
|
Sign up to set email alerts
|

Brucellosis-related acute pancreatitis: A rare complication of a universal disease

Abstract: ObjectivesTo determine the prevalence and determinants of acute pancreatitis in patients with acute brucellosis.MethodsAdult patients with brucellosis were retrospectively recruited. Brucellosis and acute pancreatitis were diagnosed according to standard criteria. Laboratory analyses included Wright agglutination titre, serum biochemical parameters and blood count.ResultsPatients with acute pancreatitis (n = 21) had significantly higher Wright agglutination titres, alanine aminotransferase, aspartate aminotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Also, gastrointestinal involvement manifests as pancreatitis and cholecystitis. These complications have been rarely reported in patients with brucellosis (24,25). Also, in our study, epididymo-orchitis presented with testicular pain and dysuria, as reported in previous studies (26).…”
Section: Discussionsupporting
confidence: 87%
“…Also, gastrointestinal involvement manifests as pancreatitis and cholecystitis. These complications have been rarely reported in patients with brucellosis (24,25). Also, in our study, epididymo-orchitis presented with testicular pain and dysuria, as reported in previous studies (26).…”
Section: Discussionsupporting
confidence: 87%
“…Sporadic cases of AP due to gastrointestinal bacteria like Campylobacter jejuni [ 35 , 36 ], Yersinia enterocolitica [ 37 , 38 ], Yersinia pseudotuberculosis [ 38 ], Brucella [ 39 ], and Nocardia [ 40 ] have been reported in the literature [ 6 ].…”
Section: Bacterial Causes Of Apmentioning
confidence: 99%
“…Inflammatory changes are probably due to a direct effect of the bacteria in the blood stream, causing the local activation of inflammatory mediators, and an indirect effect through a systemic hypercoagulable state [138]. Legionellosis [140] and brucellosis [141] infections caused by gastrointestinal pathogens (Campylobacter jejuni, Yersinia enterocolitica) were reported in association with AP [142,143].…”
Section: Bacterial Infectionsmentioning
confidence: 99%